Stephen Petronio Company Review from the Festival's Anniversary Season - Hutera, Donald (Dance Books Ltd., Alton,Hampshire (UK), 2003)
Review from the Dance Umbrella Festival's Anniversary Season. PALABRAS CLAVE: Stephen Petronio Company, September 11 2001, Edgar Allan Poe, City of Twist, Laurie Anderson, The Island Of Misfit Toys.
Dentro del apartado "Silver Jubilee: Dance Umbrella at 25".